Research on medical practices (ROMP): Attitudes of IRB personnel about randomization and informed consent - Porter, KM; Cho, MK; Kraft, SA; Korngiebel, DM; Constantine, M; Lee, SSJ; Kelley, M; James, C; Kuwana, E; Meyer, A; Diekema, D; Capron, AM; et al. (Hastings Center, 2017)
Activities such as continuous quality improvement, comparative effectiveness research, and electronic medical record review—collectively referred to as research on medical practices (ROMP)—are posing more and more challenges for meeting regulatory requirements governing research with humans. In 2014, the Office for Human Research Protections issued draft guidance to address inconsistent interpretations of how regulatory rules apply to ROMP that uses a randomized approach. That guidance has not been finalized, however, and differing regulatory interpretations persist. It is unknown whether institutional review board (IRB) personnel view ROMP differently from how they view research evaluating new treatments, particularly when ROMP involves randomization of patients to existing modes of usual care. In this study, we surveyed individuals with experience as IRB personnel about ROMP in order to better understand where there are differing opinions about IRB review and informed consent for ROMP. We used a self-administered online survey to collect data from members of Public Responsibility in Medicine and Research (PRIM&R;), a professional organization that includes IRB personnel, researchers, and others interested in the protection of human research subjects. We found that PRIM&R; members with experience as IRB personnel expressed varying views when responding to three key issues: what triggers IRB review, who should obtain consent, and when consent can be waived. Additional guidance for IRB personnel regarding activities at the intersection of clinical care and research, including ROMP and quality improvement, is essential to promote consistent interpretation of the regulations across IRBs.